2022
DOI: 10.3390/ijerph19074026
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Intimate Partner Violence and Non-Partner Sexual Violence with Hypertension in South African Women

Abstract: This study describes associations of intimate partner violence (IPV), non-partner sexual violence (NPSV) and sexual harassment (SH) exposures with hypertension in South African women aged 18–40 years. Baseline data (n = 1742) from the Rape Impact Cohort Evaluation study, including a history of sexual, physical, emotional and economic IPV, NPSV and SH were examined. Hypertension was based on blood pressure ≥140/90 mmHg or a previous diagnosis. Logistic regressions were adjusted for traditional hypertension risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…A total of 569 potentially eligible titles and abstracts across databases were screened and after excluding duplicates and those that did not meet this eligibility criteria, included 20 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] studies for data extraction and analysis (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 569 potentially eligible titles and abstracts across databases were screened and after excluding duplicates and those that did not meet this eligibility criteria, included 20 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] studies for data extraction and analysis (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Sexual and gender-based violence encompasses various acts such as sexual assault, rape, intimate partner violence, and harmful traditional practices, all of which have severe physical and psychological consequences for women [9,11,12]. The sub-Saharan Africa region has witnessed numerous cases of SGBV perpetrated against vulnerable populations, such as women, children, refugees, and individuals with disabilities, with devastating impacts on their well-being and overall quality of life [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationship between these two burdens is imperative for early screening and interventions to prevent the development of CMD. However, there have been no prospective studies examining the link between childhood and adulthood abuse and CMD in young South African women [18,19]. Accordingly, this study tested the hypothesis that exposures to abuse in childhood and adulthood were associated with poor CMD outcomes such as raised body mass index (BMI), waist circumference (WC), blood pressure (BP), and glycated haemoglobin (HbA1c) levels, and abnormal lipids pro les over a 3-year period among 18-40-year-old women exposed versus unexposed to rape at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…South Africa takes fourth place globally in terms of excessive acts of gendered violence (Yesufu 2022 :96), and this is an extremely concerning position the country finds itself in. Of the various types of gender-based violence (GBV), intimate partner violence (IPV) is a considerably rampant type of GBV (Nguyen et al 2022 :2), and has been found to affect 20% to 50% of women in South Africa (Sere, Roman & Ruiter 2021 :2). The high levels of underreporting make it difficult to determine the exact figures.…”
Section: Introductionmentioning
confidence: 99%